2017
DOI: 10.1093/molbev/msx211
|View full text |Cite
|
Sign up to set email alerts
|

Inferring Past Environments from Ancient Epigenomes

Abstract: Analyzing the conditions in which past individuals lived is key to understanding the environments and cultural transitions to which humans had to adapt. Here, we suggest a methodology to probe into past environments, using reconstructed premortem DNA methylation maps of ancient individuals. We review a large body of research showing that differential DNA methylation is associated with changes in various external and internal factors, and propose that loci whose DNA methylation level is environmentally responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 101 publications
0
39
0
Order By: Relevance
“…Environmentally-induced methylation variation can reflect environmental conditions such as food availability (e.g., Heijmans et al 2008), climate (e.g., Fu et al 2010;Gugger et al 2016), and exposure to disease or toxins (Robertson 2005;Baccarelli and Bollati 2009). Gokhman et al (2017) demonstrated how methylation patterns can be used to study past environments by describing markers of prenatal nutrition in Denisovan and Neanderthal genomes. Ancient and historic epigenomic studies may allow us to explore aspects of past populations that are not reflected in a specimen's morphology or genetic sequence.…”
Section: Applications Of Epigenomic Data From Historic Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmentally-induced methylation variation can reflect environmental conditions such as food availability (e.g., Heijmans et al 2008), climate (e.g., Fu et al 2010;Gugger et al 2016), and exposure to disease or toxins (Robertson 2005;Baccarelli and Bollati 2009). Gokhman et al (2017) demonstrated how methylation patterns can be used to study past environments by describing markers of prenatal nutrition in Denisovan and Neanderthal genomes. Ancient and historic epigenomic studies may allow us to explore aspects of past populations that are not reflected in a specimen's morphology or genetic sequence.…”
Section: Applications Of Epigenomic Data From Historic Specimensmentioning
confidence: 99%
“…Around a dozen paleoepigenetic studies have been published to date (Briggs et al 2010;Llamas et al 2012;Gokhman et al 2014;Pedersen et al 2014;Smith et al 2014Smith et al , 2015Orlando and Cooper 2014;Seguin-Orlando et al 2015;Gokhman et al 2016;Hanghøj et al 2016;Gokhman et al 2017;Murphy and Benítez-Burraco 2018). To our knowledge, all previous studies have focused on ancient DNA from paleontological and archaeological specimens rather than "historic DNA" from museum specimens collected by naturalists in the modern era, which range from decades old to a few centuries old.…”
mentioning
confidence: 99%
“…In order to investigate the methylation pattern of PCSK9 in Archaic and modern humans, we downloaded the three whole‐genome bisulfite sequencing bone methylation maps from a chimpanzee and two modern humans, and six reconstructed methylation maps from a Neanderthal, a Denisovan and four ancient modern humans (La Braña, Loschbour, Stuttgart and Ust’‐Ishim) from GEO under accession number: https://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?acc=GSE96833, as described by Gokhman et al ., .…”
Section: Methodsmentioning
confidence: 99%
“…Whilst methods to identify epigenetic changes from aDNA are only beginning to be applied (Gokhman et al 2017), and have not currently been used to study Richard, it is possible that the periods of violence and instability he experienced would have had had a lasting effect on his epigenome. For example, witnessing violence as a child has been associated with shortened telomeres (Oliveira et al 2016), as has the death of a father (Mitchell et al 2017), whilst stressful life events in childhood have been associated with hypermethylation (Soares et al 2017).…”
Section: Local Biology Embedded Bodies and Relational Personhood In mentioning
confidence: 99%